Engineering Behavior of Municipal Solid Waste Incinerated Ash with Compressible Soil: An Approach Towards the Waste Utilization & Stabilization of Compressible Soil - Saurabh Kumar; Sneha Gupta (Mechanics of Advanced Composite Structures)
The objective of the current study is to improve the strength and drainage capabilities of compressible clayey soil through the utilization of waste-to-energy plant ash. Numerous experiments, including consistency limits tests, compaction tests, unconfined compressive strength, California bearing ratio tests, and permeability tests, have been carried out in the laboratory on various combinations of highly compressible clayey soil and waste-to-energy plant ash or Municipal solid waste incinerated ash. The trial testing results show that adding waste to energy plant ash mix with the soil sample improves the strength properties of clayey soil, reducing the issue of ash dumping as well as developing a healthy environment. According to the test results, the falling head permeability test shows an improvement of permeability from 6.2×10-6 to 5.85×10-5 cm/sec for soil and soil with 20% MSWI ash mixed proportion respectively. Moreover, the mix produced by adding incineration plant ash may effectively be used as a sub-grade material, achieving cost-effective benefits. The findings showed that adding an adequate amount of bottom ash (20%) and soil sample (80%) made the soil more effective as a subgrade material by decreasing the value of differential free swell and consistency limitations of the soil and the value of UCS increased by more than 146 % and the soaked CBR values increased by 118% was noticed. The leaching test showed that when up to 20% of the ash is combined with the soil, the concentration of heavy metals lies within acceptable limits.